Changes in Shoulder Rotator Strength After Arthroscopic Capsulolabral Reconstruction in Patients With Anterior Shoulder Instability. Issue 1 (20th January 2021) - Rhee, Sung-Min; Nashikkar, Piyush Suresh; Park, Joo Hyun; Jeon, Young Dae; Oh, Joo Han
Background: The correlation between isokinetic internal and external rotation (IR and ER) strength and functional outcomes in patients with anterior shoulder instability treated by arthroscopic capsulolabral reconstruction (ACR) has not been studied. Purpose: To analyze isokinetic IR and ER strength and their correlation with clinical outcomes in patients with anterior shoulder instability treated by ACR. Study Design: Case series; Level of evidence, 4. Methods: Between January 2004 and June 2015, a total of 104 patients who underwent ACR for anterior shoulder instability were analyzed. The mean peak torque (PT) in IR (IRPT ) and ER (ERPT ), PT deficit (PTD; %) relative to the opposite healthy shoulder, and PT ratio (PTR; ERPT /IRPT ) were calculated before and 1 year after surgery. Functional scores were evaluated before surgery and at every follow-up visit. Recurrence and postoperative apprehension during ER at 90° of arm abduction were evaluated at 1 year and the final follow-up (76.6 ± 64.4 months). Results: IR and ER strength were measured for 68 of 104 patients at 1 year after surgery. ERPT and IRPT were less on the involved side than on the uninvolved side before surgery (0.29 ± 0.10 vs 0.33 ± 0.10 N·m/kg, respectively, for ERPT [ P = .002]; 0.36 ± 0.14 vs 0.41 ± 0.16 N·m/kg, respectively; for IRPT [ P = .01]). At 1 year after surgery, IRPT on the involved side recovered (0.40 ± 0.20 N·m/kg), whereas ERPT remained weak (0.30 ± 0.13 N·m/kg) relative to the baseline value. PTD in IR (PTDIR ) improved to 2.2% ± 24.4% ( P = .012), whereas PTD in ER (PTDER ) showed no improvement (13.5% ± 13.8%; P = .569). PTR on the involved side improved from 1.07 ± 1.71 to 0.86 ± 0.23 at 1 year ( P < .001). All functional scores improved significantly at the final follow-up. At 1 year, 9 of 68 (13.2%) patients showed positive apprehension. PTDIR and PTDER on the involved side were worse in patients with positive apprehension than in those with negative apprehension ( P = .039 and .014, respectively). PTDER was worse than PTDIR in patients with positive apprehension at 1 year ( P = .022). Conclusion: For those with anterior shoulder instability, preoperative IR and ER strength of the involved shoulder were lower than those of the uninvolved shoulder. IRPT recovered, whereas ERPT remained weak after ACR. To prevent positive apprehension after surgery, IR and ER strengthening exercises are important, with more emphasis on exercises for ER.